Increased risk for clinical onset of myasthenia gravis during the postpartum period - Boldingh, Marion I. (Neurology, 2016)
OBJECTIVE: To study the risk of clinical onset of myasthenia gravis (MG) in pregnancy and during the first 6 months postpartum because an association between pregnancy or the postpartum period and the onset of autoimmune MG is widely assumed but not proven. METHODS: The design was a cross-sectional population-based cohort study of 2 MG cohorts (Norway and the Netherlands) with 1,038 healthy controls from Norway. Data were obtained on 246 women with MG (age at onset 15–45 years). Data on pregnancy, hormonal factors, and clinical symptoms were collected by a previously validated environmental MG questionnaire. Relative risk of MG onset before, during, and after pregnancy was calculated by multinomial logistic regression for Norwegian women reaching 45 years of age, adjusted for the observed distribution of person-years in the corresponding control group. RESULTS: Of the included women with MG, 13 (11.5%) of the Dutch and 24 (18.0%) of the Norwegian patients had their first myasthenia symptoms during the pregnancy or postpartum period. The postpartum period was confirmed to be significantly associated with the onset of symptoms of MG in Norwegian women with MG (relative risk 5.5, 95% confidence interval 2.6–11.6). The risk was highest after the first childbirth. CONCLUSIONS: Women have a high-risk period for the onset of clinical symptoms of MG in the postpartum period, in particular after the first childbirth. Future studies should aim at elucidating the role of the hormonal-immunological-genetic interaction in the pathogenesis of MG.